Threatening of Invasive Alien Species (IAS) on Vegetation Structure and Aerial Arthropod Diversity in Protection Area of UB Forest - Amalia Fadhila Rahma; Endang Arisoesilaningsih (Indonesian Journal of Environment and Sustainable Development, 2017)
The aim of this study was to determine the vegetation structure of IAS and diversity of aerial arthropod under two level of invaded area. This study used quantitatively vegetation analysis methods for herbaceous, shrubs and tree plants through purposive plants sampling technique. Sampling areas were selected on two areas, divided into less and high invaded area of IAS. In each area, four sampling plots were randomly distributed with size 10x10 m2 using nested sampling method. All plots area were marked using GPS and then identified, documented and calculated their density and dominance. Moreover, sampling arthropod was collected by sticky bite trap with white bread, rotten bananas and jackfruit as atractant. Invasive exotic plants found in sampling areas were Debregeasia orientalis, Brugmansia suaveolen, Debregeasia longifolia and Araliaceae. Aerial arthropod as pest were found both in less and high invaded area. Therefore, classification of protected forest in UB Forest vegetation is semi-natural system.Keywords: arthropod, exotic, invasive alien species, UB Forest